Potential for Direct Interspecies Electron Transfer in Methanogenic Wastewater Digester Aggregates - Masahiko Morita (American Society for Microbiology, 2011)
ABSTRACT Mechanisms for electron transfer within microbial aggregates derived from an upflow anaerobic sludge blanket reactor converting brewery waste to methane were investigated in order to better understand the function of methanogenic consortia. The aggregates were electrically conductive, with conductivities 3-fold higher than the conductivities previously reported for dual-species aggregates of Geobacter species in which the two species appeared to exchange electrons via interspecies electron transfer. The temperature dependence response of the aggregate conductance was characteristic of the organic metallic-like conductance previously described for the conductive pili of Geobacter sulfurreducens and was inconsistent with electron conduction through minerals. Studies in which aggregates were incubated with high concentrations of potential electron donors demonstrated that the aggregates had no significant capacity for conversion of hydrogen to methane. The aggregates converted formate to methane but at rates too low to account for the rates at which that the aggregates syntrophically metabolized ethanol, an important component of the reactor influent. Geobacter species comprised 25% of 16S rRNA gene sequences recovered from the aggregates, suggesting that Geobacter species may have contributed to some but probably not all of the aggregate conductivity. Microorganisms most closely related to the acetate-utilizing Methanosaeta concilii accounted for more than 90% of the sequences that could be assigned to methane producers, consistent with the poor capacity for hydrogen and formate utilization. These results demonstrate for the first time that methanogenic wastewater aggregates can be electrically conductive and suggest that direct interspecies electron transfer could be an important mechanism for electron exchange in some methanogenic systems. IMPORTANCE The conversion of waste organic matter to methane is an important bioenergy strategy, and a similar microbial metabolism of complex organic matter in anaerobic soils and sediments plays an important role in the global carbon cycle. Studies with laboratory cultures have demonstrated that hydrogen or formate can serve as an electron shuttle between the microorganisms degrading organic compounds and methanogens. However, the importance of hydrogen and formate as intermediates in the conversion of organic matter to methane in natural communities is less clear. The possibility that microorganisms within some natural methanogenic aggregates may directly exchange electrons, rather than producing hydrogen or formate as an intermediary electron carrier, is a significant paradigm shift with implications for the modeling and design of anaerobic wastewater reactors and for understanding how methanogenic communities will respond to environmental perturbations.